Chronic Pain Assessment: A Seven-Factor Model - Megan A Davidson; Dean A Tripp; Leandre R Fabrigar; Paul R Davidson (Pain Research and Management)
BACKGROUND: There are many measures assessing related dimensions of the chronic pain experience (eg, pain severity, pain coping, depression, activity level), but the relationships among them have not been systematically established.